Tuberculosis screening, isoniazid preventive therapy coverage and factors associated with active TB diagnosis among people living with HIV at public health facilities of central Ethiopia - Mecha Aboma; Bayisa Abdisa; Gudata Imana; Kefyalew Taye; Gonfa Moti; Merob Fufa (PLoS ONE, 2025)
Introduction TB is the most frequent opportunistic infection and cause of death among People living with HIV/AIDS. Human immunodeficiency virus-positive individuals are routinely screened for tuberculosis as a means of monitoring efforts to mitigate the consequences of the disease on HIV-positive patients. TB status assessment identifies HIV-positive clients who show no evidence of active TB by symptom screening and would benefit from treatment with isoniazid for prevention of TB disease among HIV positives. Methods A facility-based cross-sectional study design was conducted in public health facilities of West Shewa Zone from January to February 2019. Of the 28 Public health facilities providing HIV/AIDS care and support (HCT and ART services) 13 of them were selected by simple random sampling techniques. Finally, 815 study participants were recruited by systematics sampling techniques & proportional sample size allocation was applied depending on the HIV patient load in each health facility. After reviewing relevant literature, a structured questionnaire adapted from standardized WHO guidelines, prepared for monitoring & evaluation of TB/HIV activities was used to collect data via interviewer. Results Of the total, 769 (94.4%) PLHIV were screened for tuberculosis, among which 212 (27.6%) were found to be positive for active tuberculosis. Among 557 (72.4%) individuals eligible for IPT, only 300 (53.9%) were provided IPT; 257 (46.1%) eligible PLHIV were not provided IPT. Resident (adjusted odds ratio [AOR] 5.6), those who didn’t attend school (AOR 4.0), primary school (grade 1-8) (AOR 3.2), and secondary school (grade 9-12) (AOR 4.2) were significantly associated with the likelihood of tuberculosis infection. Conclusion The present study findings demonstrated that tuberculosis screening for PLHIV at West Shewa Zone public health facilities was improved in comparison with reports from many African countries and other parts of Ethiopia. The IPT implementation rate fell short of both national and WHO guidelines, notwithstanding this improvement. In the study area, diagnostic methods for tuberculosis and existing preventive measures should be improved overall.